Analysis Of The Fraud Pentagon Factors In Influencing Financial Statement Fraud: Digital Maturity As A Moderating Variable - Heidi Pakpahan; Hisar Pangaribuan; Mila Susanti (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study examines the effect of the fraud pentagon framework on financial statement fraud by incorportating digital maturity as a moderating variable. The research analyses banking companies listen on the Bursa Efek Indonesia during the 2022-2024 period. A purposive sampling technique was applied in selecting the sample, resulting in 35 companies as the units of analysis. Hypothesis testing was conducted using regression analysis. The empirical findings indicate that arrogance measure by the number of CEO photographs disclosed in annual reports, has a statistically significant effect on financial statement fraud. In contrast, pressure, opportunity, rationalization, and competence do not demonstrate a significant relationship with financial statement fraud. Furthermore, digital maturity is not proven to significantly moderates the relationship between the elements of the fraud pentagon and financial statement fraud.